Recovery of Severe Acute Kidney Injury in a Patient with COVID-19: Role of Lung Ultrasonography - Varun Madireddy; Daniel W. Ross; Deepa A. Malieckal; Shamir Hasan; Azzour Hazzan; Hitesh H. Shah (CINQUILL Medical Publishers Inc., 2022)
Acute kidney injury (AKI) is recognized as a complication of COVID-19 among hospitalized patients. Lung ultrasonography (LUS) can be a useful tool in the management of COVID-19 pneumonia when interpreted correctly. However, the role of LUS in management of severe AKI in the setting of COVID-19 remains to be defined. We report a 61-year-old male who was hospitalized with acute respiratory failure from COVID-19 pneumonia. In addition to requiring invasive mechanical ventilation, our patient developed AKI and severe hyperkalemia requiring urgent dialytic therapy during his hospital stay. Our patient remained dialysis dependent despite subsequent recovery of lung function. Three days following discontinuation of mechanical ventilation, our patient developed a hypotensive episode during his maintenance hemodialysis treatment. A point of care LUS performed soon after the intradialytic hypotensive episode found no extravascular lung water. Hemodialysis was discontinued and the patient was initiated on intravenous fluids for one week. AKI subsequently resolved. We consider LUS an important tool in identifying COVID-19 patients that would benefit from intravenous fluids following recovery of lung function.